The influence of knowledge, skills and abilities on the competency of fitness centre managers - Abdullah, Mohd Firdaus; Md Yusop, Mohd Nizam; Aman, Mohd Salleh; Nazarudin, Mohamad Nizam; Abu Bakar, Abu Yazid; Wan Ibrahim, Nik Rahila; Ismail, Erwan (Malaysia Association of Research and Education for Educators, 2023)
This study was to identify the critical nature of knowledge, abilities, capabilities, and competencies in the management of fitness centers in Malaysia. This study is significant from a broad perspective for the development and growth of the fitness industry, particularly in Malaysia, as well as for the agencies and departments responsible for policy formulation. Method: The researchers gathered data through quantitative methods, interviewing a total of 600 managers of fitness centers in the Federal Territory of Kuala Lumpur, Putrajaya, and Selangor, the focus of fitness centers. Result: The study's findings indicate that the majority of managers view knowledge, skills, abilities, and competencies as 'critical' or 'very critical' to ensuring the quality management of fitness service provider centers. Conclusion: Each fitness center manager must possess specific elements within the variables or components of knowledge, skills, abilities, and competencies. The success of fitness center managers is no longer solely dependent on fitness knowledge. but they must also fully comprehend the importance of management skills such as marketing methods, operational operations, and financial management, as well as other issues affecting their fitness center. This study recommends in order to provide top quality services and run an efficient organization, each manager must have a strong knowledge base, capabilities, and competences. A manager must have the capacity to produce high-quality products or services, the ability to sell and advertise items as well as an understanding of customers' capacities as well as the ability to manage a company's finances.